MISMANAGEMENT DALAM PENCEGAHAN KEKERASAN TERHADAP PEREMPUAN DAN ANAK OLEH DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DP3A) KOTA SEMARANG - Vidyadhari Prastita Larasati; Dyah Lituhayu; Endang Larasati Setianingsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Abstract. Cases of violence experienced by women and children are increasing every year. Protection of women and children is an agenda that must be implemented, one of which is through preventing violence. This study aims to analyze the management and inhibiting factors for preventing violence against women and children conducted by DP3A Semarang City. This research uses qualitative methods by collecting data through observation, interviews and documentation. The research results show that mismanagement still occurs because the implementation of management functions is not optimal. The planning stages set objectives based on the Semarang City RPJMD. The formulation of violence prevention plans is carried out using open management principles involving JPPA, PPTK, and the Children's Forum. The implementation of violence prevention activities is prioritized in areas with high levels of violence according to the mapping results. DP3A has not yet formed an SOP for preventing violence. At the organizing stage there is a Women and Children Protection Division which is tasked with preventing and handling violence. Coordination was carried out involving LPMK, PKK, Health Service, Education Service, Babinsa, Babinkamtibmas, and Psychologists. At the briefing stage, coaching is carried out for PPTK and JPPA. Democratic leadership is implemented by the Head of DP3A in an effort to direct its members. Communication is carried out both directly and indirectly through social media. The stages of supervision are carried out in a top down manner by reviewing written reports and providing corrective actions. Inhibiting factors consist of the quantity and quality of human resources, limited budget, absence of SOPs, lack of public awareness, and underutilization of IT in violence prevention methods. Recommendations that can be given are adding employees, reviewing the budget, forming SOPs, and utilizing IT